Synergy of BAZNAS, LAZNAS, and BWI: Exploring the Potential of Zakat and Waqf for Social and Economic Welfare - Afifah, Yasmin; Ragilita, Rizkie; Pranata, M. Harry (Lembaga Riset Mutiara Akbar (LARISMA), 2023)
This study aims to analyze the role and function of zakat and waqf institutions in Indonesia, namely BAZNAS, LAZNAS, and BWI, in managing zakat and waqf in order to provide optimal benefits to the community. This study uses a qualitative method with a literature study approach, with primary data sources in the form of Law Number 23 of 2011 concerning Zakat Management and Law Number 41 of 2004 concerning Waqf, as well as secondary data sources from books, scientific journals, and official publications of related institutions. The results of the study indicate that BAZNAS and LAZNAS have an important role in managing zakat, from collection, distribution, to utilization, while BWI plays a role in developing and advancing waqf in Indonesia, including the management of productive waqf. This study highlights the importance of credibility and accountability in zakat management, as well as the potential of waqf as an instrument for empowering the people's economy.